2018
DOI: 10.1371/journal.pone.0202277
|View full text |Cite
|
Sign up to set email alerts
|

A positive attitude towards provision of end-of-life care may protect against burnout: Burnout and religion in a super-aging society

Abstract: AimThe aim of our study was to investigate factors associated with burnout of nurses and care workers in nursing homes and geriatric hospitals in Japan. The use of Buddhist priests, the major religion in Japan, was also explored.MethodsQuestionnaires for nurses and care workers were sent to 10 care facilities. The survey questions included basic demographic information, the Japanese Burnout Index and the Japanese version of the Frommelt Attitude Toward Care Of Dying Scale Form B. They also asked questions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Additionally, the present study showed that the level of performance of EOL care were significantly lower in nurses who were younger, or had fewer years of experience, as compared to their older or more experienced colleagues. This finding supported the results of previous studies that younger nurses may have stronger fear or psychological burden for death or the dying process and consequently, more negative attitudes toward EOL care [12,15]. The experience of unpredictable and stressful environments might be more uncomfortable to novice nurses who have relatively insufficient education in the area of EOL care [8,41].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, the present study showed that the level of performance of EOL care were significantly lower in nurses who were younger, or had fewer years of experience, as compared to their older or more experienced colleagues. This finding supported the results of previous studies that younger nurses may have stronger fear or psychological burden for death or the dying process and consequently, more negative attitudes toward EOL care [12,15]. The experience of unpredictable and stressful environments might be more uncomfortable to novice nurses who have relatively insufficient education in the area of EOL care [8,41].…”
Section: Discussionsupporting
confidence: 89%
“…Hospital nurses in acute care hospitals are frequently exposed to dying patients and death in their workplace [3,8]. Notwithstanding that a patient's death is one of the most common stressors in clinical settings, nurses are unlikely to express their feelings and evaluations about such occurrences with their colleagues [10][11][12]. Prior studies have reported that nurses had feelings of inadequacy, helplessness, or distress in supporting dying patients [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the content analysis of literature, a total of 18 probable impact factors 5–7,14,15,19,25–50 were discussed, and 130 knowledge items, 5,6,21,26,32,36,51 206 attitude items, 6–8,13,15,21,25,32‐35,39,44–46,48,50–53 and 37 practice items 21,26,47 were identified. Thus, the original draft of KAPHC Scale consisted of 18 demographic items, 22 knowledge items, 24 attitude items, and 22 practice items in Phase I, with the CVI of 0.930.…”
Section: Resultsmentioning
confidence: 99%
“…3 In Japan, a positive attitude toward providing end-of-life care was identified as a protective factor against depersonalization, which is a subcategory of burnout. 4 Given that health is a state of complete physical, mental and social well-being, rather than simply the absence of illness or disability, the mental well-being of care staff is an important factor that has not been sufficiently explored in comparison with burnout. 5 In Japan, Inatani et al carried out a survey among staff of longterm care facilities using the General Health Questionnaire-28, which is usually used as a screening tool to detect mental illness.…”
mentioning
confidence: 99%